STRATEGI PEMERINTAH DAERAH DALAM PEMBANGUNAN PARIWISATA DI PROVINSI NUSA TENGGARA BARAT - aos Kuswandi (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
This study aims to explain the local government's strategy in tourism development in East Nusa Tenggara Province, with a focus on: identifying tourism potential; leading tourism areas and destinations; identification of tourism problems; and local government strategies to achieve successful tourism development. This research uses descriptive analysis method. Data were collected through literature studies and documentation studies. Data obtained from secondary data through internet footprints based on the website of the West Nusa Tenggara Provincial Government and other related institutions. The results of the study concluded that first, West Nusa Tenggara Province was able to achieve the success of tourism development through a tourism potential identification strategy; determination of leading tourism destinations; stipulation of regional tourism strategy areas; and formulation of Regional Tourism Development Master Plans; The Tourism Office's Strategic Plan and the Tourism Office's Performance Plan, second, the tourism development planning system is formulated in stages, synergies and involves multi-stakeholders; third, sustainable tourism development through changing poor villages into tourist villages; fourth, developing tourism infrastructure and supporting facilities; marketing through tourism promotion; establish partnerships; improving the quality of tourism human resources; increasing the number and quality of tourism attractions. Keywords: Local Government Strategy; Tourism Development; Regional Tourism Strategic Areas; Tourism Destinations.